Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.3389/fpsyg.2017.00549
|View full text |Cite
|
Sign up to set email alerts
|

Social Behavior of Pet Dogs Is Associated with Peripheral OXTR Methylation

Abstract: Oxytocin is a key modulator of emotional processing and social cognitive function. In line with this, polymorphisms of genes involved in oxytocin signaling, like the oxytocin receptor (OXTR) gene, are known to influence social behavior in various species. However, to date, no study has investigated environmental factors possibly influencing the epigenetic variation of the OXTR gene and its behavioral effects in dogs. Pet dogs form individualized and strong relationships with their owners who are central figure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 80 publications
3
23
0
1
Order By: Relevance
“…Epigenetic studies in humans have found altered DNA methylation in the 5′ CpG island of OXTR in a wide spectrum of morbid behaviors and neuropsychiatric disorders, such as autism spectrum disorder (ASD), schizophrenia, bipolar, depression, obsessive-compulsive disorders (OCD), and anxiety (12)(13)(14)(15)(16)(17)(18). Similar correlations between DNA methylation and behavior are also reported in other species, such as dog and nonhuman primates (19,20).…”
Section: Introductionmentioning
confidence: 56%
“…Epigenetic studies in humans have found altered DNA methylation in the 5′ CpG island of OXTR in a wide spectrum of morbid behaviors and neuropsychiatric disorders, such as autism spectrum disorder (ASD), schizophrenia, bipolar, depression, obsessive-compulsive disorders (OCD), and anxiety (12)(13)(14)(15)(16)(17)(18). Similar correlations between DNA methylation and behavior are also reported in other species, such as dog and nonhuman primates (19,20).…”
Section: Introductionmentioning
confidence: 56%
“…While evidence has already been found that dogs behaving differently have different methylation levels (Cimarelli et al, 2017), it is yet to be examined how these different methylation levels emerge as a result of environmental influence, as for example no effect of owner interaction style on methylation levels was found.…”
Section: Discussionmentioning
confidence: 99%
“…Another study from the same group analysed buccal samples of nine dogs (from six different breeds and three mixed breeds) and three timber wolves (Cimarelli et al, 2017) Weak gender-specific associations with methylation level. Female dogs had higher methylation levels than males in position −1371, males had higher methylation levels than females in position −727.…”
Section: Associations Between the Polymorphisms In Oxytocin Receptor mentioning
confidence: 99%
“…This is a new area of research, and studies on dog behaviour and epigenetic factors are scarce. As the first of its kind, Cimarelli, et al (180) could associate dog's social behaviour to DNA methylation of the oxytocin receptor gene. In males, a lower methylation level was associated with approaching a threatening stranger and a higher level with hiding behind their owner.…”
mentioning
confidence: 99%
“…Interestingly, Cimarelli, et al (180) also tested if owner interaction style affects methylation of dog's oxytocin receptor gene. They did not find an association between the two.…”
mentioning
confidence: 99%